High score - Howell, Destiny (Scholastic Press, 2022)
After running afoul of school officials at his last school, twelve-year-old DJ has moved to a new school and retired from a life of running schemes and cons. However, when his former best friend Conor is also transferred there, it turns out Conor is in trouble with the school kingpin running an underground trade of Starcade tickets. Conor is threatened with being socially exiled if he doesn't come up with 100,000 Starcade tickets in a matter of weeks. In order to save his friend, DJ organizes an elaborate heist to lift tickets from a local Starcade, enlisting the help of some new friends.